Dawn of artificial intelligence -Enable digital Pathology in Pakistan-A paradigm shift - Zehra, Talat; Shaikh, Asma; Shams, Maheen (Journal of the Pakistan Medical Association, 2021)
Pathology particularly histopathology is considered to be a busy and challenging field. It is considered as gold standard for the diagnosis and management of patient particularly in cases of tumor. It has been more than twenty years since the introduction of whole slide imaging (WSI) in the developed part of the world. Various whole slide image (WSI) devices and use of artificial intelligence (AI) based softwares have transformed the field of Pathology1. Digital pathology is a novel technology and currently being implemented in most of the developed part of the world.2 Once the patient’s data becomes digital, it is easily stored, reproducible on a single click and quality remains same. This data can be used to make disease models, disease trends and predict the outcome of a particular disease through data mining which will open new horizons of precise medicine. The use of WSI with computational pathology and data storage devices have revolutionized the working in histopathology. The world witnessed an exponential rise in its adoption particularly after Covid-19 pandemic1. However, in the developing world either it is not being implemented or its use is still sub-optimal. By realizing the potential of digital and computational pathology along with the use of artificial intelligence software, we can bring a drastic change in the field of personalized medicine in the developing part of the world 3. Numerous validation studies have been published indicating that WSI is a reliable tool for routine diagnosis in surgical pathology 4 Continuous...